Productivity improvement through line balancing technique in a small medium enterprise (SME) manufacturing plant - Shahfiran, Sarifuddin (2007)
Assembly lines are flow-line production systems which are of great importance in the industrial production of high quantity standardized commodities and more recently even gained importance in low volume production of customized products. In Small Medium Enterprise (SUE) manufacturing plant, assembly line gives high impact to the productivity of the company. Less of skill and knowledge in management in the company make the SUE cannot compete to large company. This project is important to SUE company to solve the problem. The main objective of this project is to improve the productivity of the specific company by using software simulation. In this project, line balancing technique will be used and WITNESS software will be act as a simulation tool to find the good solution for this problem. This project will be used WITNESS software to make sure that the arrangement in the-line is correct. By defining the problem that happen in the exiting line and give alternative of new assembly line, the problem will be solved.